Archipelago Traditional House Application Based on Articulate Storyline 3 in Grade Five Elementary School - Dinis Puspita Dewi; Kurniana Bektiningsih (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Traditional House learning material in content There are many Pancasila education lessons, causing results For students in low V classes. Study This aims to develop learning media from the Archipelago Traditional House Application based on Articulate Storyline 3 in class V elementary school. This research uses research and development (R&D) as a research method and ADDIE development model. Subject from study This is students, class teachers, and team experts. Data collection techniques used are test and non-test. The data analysis techniques used are descriptive qualitative and descriptive quantitative. Research data This was obtained through interviews, observations, and a questionnaire. Validation results in media experts of 92% and experts material of 91% show that The Archipelago Traditional House Application is very feasible to use. Learning outcomes pre-test and post-test show the average difference is 30, which means there are enhanced results for Study students. The average value obtained based on calculating the N-Gain score is 72%, which means the media is effective. For increased results, Study students. Response results show that media use by students is 92% and that of teachers is 90%, meaning the media is effective for application in learning. Therefore, the Archipelago Traditional House Application based on Articulate Storyline 3 is feasible for application in learning and can increase results For students in Class V Elementary School.